Reproductive ability of queen beesunder the influence of heavy metals and fatty acids of bee pollen - Yosyp RIVIS; V. О. PОSТОIENКО; І. І. SАRАNCHUК; О. І. SТАDNYTSКА; О. Ya. КLYМ; О. B. DIACHЕNКО; А. V. SHЕLЕVАCH; О. О. HОPАNЕNКО (Передгірне та гірське землеробство і тваринництво)
In the literature, there are only fragmentary data on the content of heavy metals and fatty acids in bee pollen and tissues of honey bees kept in different natural zones of the Carpathian region.